Intelligence Context Aware Mobile Navigation using Augmented Reality Technology - Ahmad Hoirul Basori; Abdullah M. Al-Ghalib Al-Sharif; Atiah O. Faraj AL-Oufi; Alaa Omran Almagrabi; Omar M. Barukab (Universitas Airlangga, 2018)
Most of the technologies of today’s world, which are enriched with various powerful features and amazing quality characteristics, enables software developers to come up with best possible software solutions, no matter what the context of the particular issue. Technologies such as Augmented Reality (AR), is utilized almost every kind of fields in today’s society. As computers become more advanced through mobile devices and wearable technology, augmented reality will become a seamless experience that is a part of our everyday lives. In the context of this work, an Intelligence mobile navigation application for the King Abdul Aziz University Rabigh is developed enabling the user to find specific locations on campus and offers the ability to explore the campus environment via AR. Furthermore, the system, Mobile Campus Navigation with Augmented Reality application is capable of giving guidance in outdoor location navigating and retrieving details of campus officials and lecturers. With the proposed system, it is expected to serve as a useful and informative navigate helper for both students of King Abdul Aziz University and for the visitors, at outdoor locations and to use as an application to check officials and lecturer availability and retrieve detail about them when they are not available at the office at any time.